High‐speed video and electromagnetic analysis of two natural bipolar cloud‐to‐ground lightning flashes. Issue 10 (28th May 2014) - Saraiva, A. C. V.; Campos, L. Z. S.; Williams, E. R.; Zepka, G. S.; Alves, J.; Pinto, O.; Heckman, S.; Buzato, T. S.; Bailey, J. C.; Morales, C. A.; Blakeslee, R. J.
Abstract High‐speed video records of two bipolar cloud‐to‐ground flashes were analyzed in detail. They both began with a single positive return stroke that was followed by more than one subsequent weak negative stroke. Due to the elevated cloud base height of its parent thunderstorm, the preparatory processes of each subsequent negative stroke were documented optically below cloud base. In the first event (Case 1) it was observed that all four subsequent negative strokes were initiated by recoil leaders that retraced one horizontal channel segment previously ionized by the positive leader. Those recoil leaders connected to the original vertical channel segment and propagated toward ground, producing four subsequent strokes that had the same ground contact point as the original positive discharge. The second event (Case 2), in contrast, presented 15 subsequent strokes that were initiated by recoil leaders that did not reach the original channel of the positive stroke. They diverged vertically toward ground, making contact approximately 11 km away from the original positive strike point. These results constitute the first optical evidence that both single‐ and multiple‐channel bipolar flashes occur as a consequence of recoil leader activity in the branches of the initial positive return stroke. For both events their total channel length increased continuously at a rate of the order of 104 m s−1, comparable to speeds reported for typical positive leaders.